BioRef II - Neutron reflectometry with relaxed resolution for fast, kinetic measurements at HZB - Trapp, Marcus; Steitz, R.; Kreuzer, Martin; Strobl, M.; Rose, M.; Dahint, Reiner (Review of scientific instruments, 2016)
We present an upgrade to the time-of-flight neutron reflectometer BioRef at the research reactor BER II of the Helmholtz-Zentrum Berlin für Materialien und Energie (HZB). Through the integration of an additional chopper into the existing setup, the available wavelength resolution is significantly extended. Now two distinct operation modes can be used: a high resolution mode with Δλ/λ ranging from 1% to 5%, which allows for the investigation of thick films up to 4000 Å, and a high flux mode with Δλ/λ = 7%-11%. In the high flux mode, reflectivity curves from 0.007 Å−1 to 0.2 Å−1 with three angular settings can be recorded in 7 min. For a single angular setting and its respective window in Q-space, a time resolution of even less than 4 min is reached. The different configurations are documented by respective measurements (a) on a Ni-Ti multilayer and (b) the swelling kinetics of a solid-supported phospholipid coating upon incubation in a polyelectrolyte solution.
Gesehen am 27.05.2020